Excursions in world music - Nettl, Bruno 1930-; Rommen, Timothy; Wong, Isabel K. F.; Capwell, Charles; Turino, Thomas; Bohlmam, Philip V.; Dueck, Byron; Jankowsky, Richard; Pilzer, Joshua D.; Sykes, Jim (New York Routledge, 2017)
The new seventh edition introduces five brand new chapters, including chapters by three new contributors on the Middle east, South Asia, and Korea, as well as a new chapter on Latin America along with a new introduction written by Timothy Rommen. General updates have been made to other among ethnomusicologists who want students to explore the in-depth knowledge and scholarship that animates regional studies of world music.--Back cover
1 Introduction: studying musics of the world's cultures -- 2 Music of South Asia -- 3 Music of the Middle East and North Africa -- 4 Music of East Asia I: China -- 5 Musics of East Asia II: Korea -- 6 Musics of East Asia III: Japan -- 7 Music of Indonesia -- 8 Music of Sub-Saharan Africa -- 9 The Musical Culture of Europe -- 10 Music in Latin America -- 11 Music in the Caribbean -- 12 Native American Music -- 13 Music of Ethnic North America -- Glossary -- Index.
International Student edition.
Includes bibliographical references, discography (page 490) and index.
Keywords: World music -- Analysis, appreciation